Phenotyping cardiomyopathy in adult zebrafish. (October 2018) - Dvornikov, Alexey V.; de Tombe, Pieter P.; Xu, Xiaolei
Abstract: Hypertrophic cardiomyopathy (HCM) is usually manifested by increased myofilament Ca 2+ sensitivity, excessive contractility, and impaired relaxation. In contrast, dilated cardiomyopathy (DCM) originates from insufficient sarcomere contractility and reduced cardiac pump function, subsequently resulting in heart failure. The zebrafish has emerged as a new model of human cardiomyopathy with high-throughput screening, which will facilitate the discovery of novel genetic factors and the development of new therapies. Given the small hearts of zebrafish, better phenotyping tools are needed to discern different types of cardiomyopathy, such as HCM and DCM. This article reviews the existing models of cardiomyopathy, available morphologic and functional methods, and current understanding of the different types of cardiomyopathy in adult zebrafish.